Dnipro Pharmacology School: a 100 years’ journey (to the centenial of the department of pharmacology and clinical pharmacology of Dnipropetrovsk medical academy). Part I: 1918-1943. - V. I. Mamchur; V. I. Zhilyuk; E. Yu. Kovalenko (Medičnì Perspektivi)
The article presents analysis of the main historical stages of the establishing and development of the scientific school of pharmacology of the SE "Dnipropetrovsk Medical Academy of Health Ministry of Ukraine" for a 100-year lifetime period of the pharmacology department. Part I (1918-1943) is devoted to one of the most important and difficult periods – the first period of development of scientific school of pharmacologists: since the establishment of the Department of Pharmacology of Katerinoslavsky Medical Institute in 1918, its first difficult steps in the organization of the department and creation of its facilities and equipment base, of establishing training process on the basics of pharmacotherapy, up to the period of formation of important scientific discoveries in experimental and clinical pharmacology and active scientific development of the whole direction of pharmacological school in the 30-40ies of the XX-th century. It is shown that during the first 25 years of scientific and pedagogical work, the department turned into a powerful scientific school, which brought up outstanding scientists of the day to the medical science of our country, and formed a generation of young students and doctors with a new worldview, with  understanding the importance and value of scientific knowledge of fundamental pharmacology, applied knowledge of rational pharmacotherapy and clinical pharmacology to improve the quality of patients’ care in practical medicine.